PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN EMOTIONAL SPIRITUAL QUOTIENT SISWA KELAS XI AKUNTANSI SMK MUHAMMADIYAH 2 PEKANBARU T.A 2014/2015 - Febri Ramadhan Febri Ramadhan; Zulfan Saam Zulfan Saam; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effect of guidance group to increase emotional spiritual quotient students of class XI SMK Muhammadiyah 2Pekanbaru TP 2014/2015. This research was conducted in SMK Muhammadiyah 2Pekanbaru from March 2015 until June 2015. The method used was experimental method to pattern one-group pretest-posttest. Population is student of class XI accounting 1 and XI accounting 2 having problems about emotional and spiritual quotient, 59 of the population taken 30 students used as research subjects (random sampling) data collection instrument used was a questionnaire using Likert scale. Data analysis technique used is the statistical correlation techniques. Based on the hypothesis test results turned out a significant influence on the improvement of guidance group to increase emotional spiritual quotient by 35% .Keywords: Effect Of Guidance Group, Emotional Spiritual Quotient (ESQ)